Revisión del significado del concepto de Industria 4.0 y los desafíos asociados a las tecnologías y sistemas de información - Rico, Mariela Guadalupe (2023)
Industry 4.0 is a strategic initiative introduced by the German government whose objective is the transformation of manufacturing and industrial connectivity, through digitization and exploitation of the potential of new technologies. Thus, an Industry 4.0 production system is flexible and allows individualized and personalized products. The aim of this paper is to present and facilitate the understanding of the Industry 4.0 concepts, the technologies that make it possible, its main characteristics, and to discuss some of the challenges that arise from the perspective of decision-making systems, interoperability, and the management of large volumes of data.